2021
DOI: 10.1111/acer.14682
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol on mood among males drinking with a platonic friend

Abstract: Background Despite the social nature of most drinking experiences, prior work has largely failed to incorporate social context into the study of alcohol's effects on emotion. The present study provides an initial test of the effect of alcohol on mood among platonic friends drinking together in a non‐stress setting. We hypothesized that subjects would report more positive postdrink mood after consuming alcohol than after consuming a nonalcoholic control beverage. Methods Dyads of platonic male friends (n = 36; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
1
2
Order By: Relevance
“…Overall, the lack of effect of the social environment on subjective effects and affect deviates from past laboratory findings demonstrating that consuming alcohol in the presence of peers was associated with greater positive affect (Bowdring & Sayette, 2021;Fairbairn et al, 2015) and stimulation (Kirkpatrick & de Wit, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall, the lack of effect of the social environment on subjective effects and affect deviates from past laboratory findings demonstrating that consuming alcohol in the presence of peers was associated with greater positive affect (Bowdring & Sayette, 2021;Fairbairn et al, 2015) and stimulation (Kirkpatrick & de Wit, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, the lack of effect of the social environment on subjective effects and affect deviates from past laboratory findings demonstrating that consuming alcohol in the presence of peers was associated with greater positive affect (Bowdring & Sayette, 2021; Fairbairn et al., 2015) and stimulation (Kirkpatrick & de Wit, 2013). In the current study, average peak blood alcohol level at the second end drink report was less than 0.04, whereas the average peak was above 0.06 for all three studies demonstrating an effect of the social context on positive affect and stimulation.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Recently, an emerging literature has begun to examine alcohol's effects in social settings. In contrast to isolated laboratory studies, this research has found alcohol to enhance emotional (e.g., Bowdring & Sayette, 2021; Fairbairn et al., 2018) and social experience (e.g., Gurrieri et al., 2021; Kirkpatrick & De Wit, 2013; Sayette et al., 2012). Such socially enhancing effects may motivate drinking.…”
Section: Introductionmentioning
confidence: 74%